Optical force on diseased blood cells: Towards the optical sorting of biological matter. (January 2016) - Gongora, Juan Sebastian Totero; Fratalocchi, Andrea
Abstract: By employing a series of massively parallel ab-initio simulations, we study how optical forces act on biological matter subject to morphological disease. As a representative case study, we here consider the case of Plasmodium falciparum on red blood cells (RBC) illuminated by a monochromatic plane wave. Realistic parameters for the geometry and the refractive index are then taken from published experiments. In our theoretical campaign, we study the dependence of the optical force on the disease stage for different incident wavelengths. We show that optical forces change significantly with the disease, with amplitude variation in the hundreds of pN range. Our results open up new avenues for the design of new optical systems for the treatment of human disease. Highlights: We calculate optical forces on red blood cells infected by malaria. We studied how optical forces interact with biological samples. We show that optical force is very sensitive to the presence of a blood infection. We show that optical forces can be used for the treatment of biological diseases.